Impact of social media's perceived online community value on user's responses - Rahman, Zoha; Suberamanian, Kumaran; Zanuddin, Hasmah; Moghavvemi, Sedigheh; Md Nasir, Mohd Hairul Nizam (2017)
Increasingly, consumers use social media as a vehicle for pre-purchase information gathering and post purchase experience sharing. Although existing social media research provides some valuable insights, it is relatively lacking in theory based research on the basic mechanisms through which desired brand goals are achieved. Value creation in online communities is a very crucial question that still needs further research. This study is an attempt to observe popular fan-pages' followers' activities of selected fan-pages of Malaysia and survey (n= 318) on followers of those fan-pages to show the impact of user's perceived online community value on their behavioral responses. The purpose of this paper is to investigate the impact of users' perceived community value on fan page engagement activities alongside the impact of fan-page engagement actions on fan-page loyalty. Besides, the impact of Fan-page loyalty on brand WOM (Word of Mouth) and purchase intention is also explored. Besides, the moderating impact of user's trust between the relationship of fan-page engagement and fan-page loyalty is also explored. The concepts of Diffusion of Innovation (DOl) theory is applied to create a unified model that was empirically validated by SEM analysis through AMOS. These findings have theoretical implications for social media and online interaction related literature as well as critical business implications for B2C (Business to Consumer) marketers to differentiate themselves within the inflating number of online platforms.